2017
DOI: 10.1007/s10354-017-0557-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gastrointestinal motility beyond metoclopramide and domperidone

Abstract: SummaryThe prokinetic cisapride, an important therapeutic option in functional gastrointestinal (GI) disorders, was withdrawn from the market 15 years ago due to rare severe side effects. Likewise in 2014, the use of metoclopramide (MCP) and domperidone in functional GI disorders (FGID) was restricted, consequently leaving a therapeutic gap in clinical practice. A systematic review revealed that the herbal medicinal product (HMP) STW 5 presents a therapeutic option equivalent to MCP and cisapride. STW 5 is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
2
Order By: Relevance
“…Taking diabetic gastroparesis as an example, as many as 25%–55% of patients with type 1 diabetes have gastroparesis, with a slightly higher incidence rate in patients with type 2 diabetes, causing great suffering and poor quality of life in patients[ 11 ]. GI motility disorder is becoming a serious public health problem and a significant burden to society; however, current treatment options for gut dysmotility are limited because of serious side effects[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking diabetic gastroparesis as an example, as many as 25%–55% of patients with type 1 diabetes have gastroparesis, with a slightly higher incidence rate in patients with type 2 diabetes, causing great suffering and poor quality of life in patients[ 11 ]. GI motility disorder is becoming a serious public health problem and a significant burden to society; however, current treatment options for gut dysmotility are limited because of serious side effects[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Следует помнить, что некоторые группы препаратов могут влиять на результаты тестирования на H. pylori, в связи с этим должны быть заблаговременно отменены, в частности антациды, препараты висмута трикалия дицитрата, ИПП. При принятии решения о начале антихеликобактерной терапии у пациентов с симптомами диспепсии всегда необходимо учитывать потенциальные побочные эффекты антибиотикотерапии, а также то, что после эрадикации H. pylori только у 10% пациентов развивается долгосрочная бессимптомная ремиссия, в то время как у остальных пациентов симптомы диспепсии довольно быстро возвращаются или сохраняются даже после того, как было достигнуто полное уничтожение H. pylori в слизистой оболочке желудка [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Reviewunclassified
“…Phytotherapeutics have been used in medicine for decades, and numerous placebo-controlled trials have shown a significantly positive effect compared to placebo in the treatment of FD [10,11]. Combination preparations are often used to treat FD.…”
Section: Introductionmentioning
confidence: 99%